Character Reduction in Literary Adaptations: Fidelity Analysis of Cinematic Translations - Rege, Satyamangal (Journal of Educational Research and Policies, 2026)
This paper focuses on studying Kenneth Branagh's 2017 Murder on the Orient Express, a film adaptation of Agatha Christie’s novel of the same name, released in 1934. Film adaptations are dynamic portrayals of words in black and white on a colourful screen. Film adaptations make amends like reduction, addition, and modification to the characters, plot, setting, and even style of the novel they are adapted from to foster a deeper understanding and bring cohesion to the portrayed scenes. A major loss of elements can be observed in film adaptations even when original stories remain intact. This paper deals with the instance of the removal of Constantine, a coroner, who in the novel declares the victim dead. Even with a small role, Constantine played a part in Christie’s imagination but seemed redundant in Branagh’s vision. The following study records Constantine's role in the novel and a comparison with the movie adaptation.